INCOME INEQUALITY IN SURAKARTA - Vita Kartika Sari; Fathimah Kurniawati (MESP–FEB UNS, 2018)
Income inequality is the crucial issue in Indonesia. Economic growth and income inequality is the main problem in Indonesia, but very view study explain it inter-subdistrict level. This argument is interesting to be studied deeply. One of the developed and famous region in Indonesia is Surakarta that has high-level income inequality. Data which is used in this research is secondary data. We used the Williamson index and enstrophy heil index to analyze income inequality inter-subdistrict, Location Quotient is used to analyze potential sectors, and Klassen Typology is used to classify quadrant of the advanced and poor zone in Surakarta.The result shows that based on the Williamson Index and Entropy Theil Index showed that Pasar Kliwon and Serengan have the highest disparity among all inter-subdistrict in Surakarta. There are three sectors that not potential during 2010-2013, they are agriculture, mining, and industries.Keywords: Local Development, Income Inequality, Surakarta